Solid-state synthesis of few-layer cobalt-doped MoS2 with CoMoS phase on nitrogen-doped graphene driven by microwave irradiation for hydrogen electrocatalysis. Issue 56 (16th September 2020) - Fan, Junpeng; Ekspong, Joakim; Ashok, Anumol; Koroidov, Sergey; Gracia-Espino, Eduardo
Abstract : Production of nanostructured cobalt-doped MoS2 flakes with the CoMoS phase by microwave irradiation with improved catalytic activity towards hydrogen evolution. Abstract : The high catalytic activity of cobalt-doped MoS2 (Co–MoS2 ) observed in several chemical reactions such as hydrogen evolution and hydrodesulfurization, among others, is mainly attributed to the formation of the CoMoS phase, in which Co occupies the edge-sites of MoS2 . Unfortunately, its production represents a challenge due to limited cobalt incorporation and considerable segregation into sulfides and sulfates. We, therefore, developed a fast and efficient solid-state microwave irradiation synthesis process suitable for producing thin Co–MoS2 flakes (∼3–8 layers) attached on nitrogen-doped reduced graphene oxide. The CoMoS phase is predominant in samples with up to 15 at% of cobalt, and only a slight segregation into cobalt sulfides/sulfates is noticed at larger Co content. The Co–MoS2 flakes exhibit a large number of defects resulting in wavy sheets with significant variations in interlayer distance. The catalytic performance was investigated by evaluating the activity towards the hydrogen evolution reaction (HER), and a gradual improvement with increased amount of Co was observed, reaching a maximum at 15 at% with an overpotential of 197 mV at −10 mA cm −2, and a Tafel slope of 61 mV dec −1 . The Co doping had little effect on the HER mechanism, but a reduced onset potential and charge transfer resistance contributed to the improved activity. Our results demonstrate the feasibility of using a rapid microwave irradiation process to produce highly doped Co–MoS2 with predominant CoMoS phase, excellent HER activity, and operational stability.